Combined crystallographic and computational investigation of the solvent disorder present in a new tipiracil hydrochloride methanol solvate–hydrate. Issue 18 (8th April 2022) - Barbas, Rafael; Font-Bardia, Mercè; de Sande, Dafne; Frontera, Antonio; Prohens, Rafel
Abstract : We report a computational and crystallographic analysis of tipiracil hydrochloride (methanol solvate–hydrate). It shows a complex network of H-bonds with static discrete disorder in two out of the three symmetry-independent solvent molecules. Abstract : This work reports a combined computational and experimental analysis of the crystal structure of the cancer drug tipiracil hydrochloride in the form of a methanol solvate–hydrate (4 : 1 : 3, molar ratio). The crystal structure shows a complex network of H-bonds with static discrete disorder in two out of the three symmetry-independent solvent molecules, which has been studied by means of DVS and TGA techniques. MEP surface calculations shows a region of positive potential (σ-hole) along the C–Cl bond, which induces the formation of Cl⋯O contacts that are relevant in the crystal packing. The hydrogen and halogen bonding assemblies were further analyzed using density functional theory (DFT), the quantum theory of "atom-in-molecules" (QTAIM) and the noncovalent interaction plot (NCIplot).